Design and optimisation of a fuzzy-PI controlled modified inverter-based PMSM drive employed in a light weight electric vehicle. (8th April 2022) - Sain, Chiranjit; Banerjee, Atanu; Biswas, Pabitra Kumar; Azar, Ahmad Taher; Babu, Thanikanti Sudhakar
In this paper, a pulse width modulation (PWM) controlled permanent magnet synchronous motor (PMSM) is designed and illustrated using fuzzy logic control. The traditional PI controller is modified as a fuzzy-PI controller for faster dynamic response. The fuzzy logic operated speed controller ensures an almost zero steady-state speed error in this proposed approach. In addition, a stochastic optimisation tool such as the updated particle swarm optimisation (PSO) technique is used to optimise the performance of the proposed fuzzy logic controller. The economical as well as robust design procedure for the buck converter fed VSI is also proposed. With the configuration of the inverter, an improved over-current protection method is developed for the permanent magnet motor in a real-time light electric vehicle. Later, the control strategy of the developed prototype is tested and verified using a low-cost microcontroller. Furthermore, to improve the robustness of the drive, sensorless speed estimation procedure is also adopted in the real-time setup. Finally, simulations and test results reveal the efficacy of this proposed approach over the existing control topologies.